Associations between the household environment and stunted child growth in rural India: a cross-sectional analysis. Issue 2 (22nd February 2021) - Lee, Charlotte; Lakhanpaul, Monica; Stern, Bernardo Maza; Sarkar, Kaushik; Parikh, Priti
Abstract : Stunting is a major unresolved and growing health issue for India. There is a need for a broader interdisciplinary cross-sectoral approach in which disciplines such as the environment and health have to work together to co-develop integrated socio-culturally tailored interventions. However, there remains scant evidence for the development and application of such integrated, multifactorial child health interventions across India's most rural communities. In this paper we explore and demonstrate the linkages between environmental factors and stunting thereby highlighting the scope for interdisciplinary research. We examine the associations between household environmental characteristics and stunting in children under 5 years of age across rural Rajasthan, India. We used Demographic and Health Survey (DHS)-3 India (2005–2006) data from 1194 children living across 109, 041 interviewed households. Multiple logistic regression analyses independently examined the association between (i) the primary source of drinking water, (ii) primary type of sanitation facilities, (iii) primary cooking fuel type, and (iv) agricultural land ownership and stunting adjusting for child age. The results suggest, after adjusting for child age, household access to (i) improved drinking water source was associated with 23% decreased odds [odds ratio (OR) = 0.77, 95% confidence interval (CI) 0.5–1.00], (ii) improved sanitation facility was associated with 41% decreased odds (OR = 0.51, 95% CI 0.3–0.82), and (iii) agricultural land ownership was associated with 30% decreased odds of childhood stunting (OR 0.70, 95% CI 0.51–0.94]. The cooking fuel source was not associated with stunting. Our findings indicate that a shift is needed from nutrition-specific to contextually appropriate interdisciplinary solutions, which incorporate environmental improvements. This will not only improve living conditions in deprived communities but also help to tackle the challenge of childhood malnutrition across India's most vulnerable communities.